The new Brazilian automotive policy and its impact on the competitiveness of multinational automobile and auto parts manufacturers - Pascoal, Erik Telles [UNESP]; Delamaro, Maurício César [UNESP]; Ibusuki, Ugo; Tsukada, Osamu; Rocha, Henrique Martins (Inderscience Publishers, 2017)
To enhance the competitiveness of the Brazilian automotive industry, the government approved a new automotive policy in October 2012. It is called the Inovar-Auto program and will be implemented over the course of five years from 2013 to 2017. This program encourages automakers and their suppliers to produce more efficient, technologically advanced vehicles and auto parts by investing in R&D and engineering. The objective of this paper is to determine whether the Inovar-Auto program will effectively improve the competitiveness of the Brazilian automotive industry. In this sense, the impact of each Inovar-Auto requirement in relation to the Porter's diamond model and flowchart approach model was investigated. Although the Inovar-Auto program represents an advance over previous industrial policies, particularly in relation to aspects concerning improvement in energy efficiency, encouraging innovation, increased local content, the traceability of auto-parts and supplier development policy, the result of this research indicates that its implementation has not been stimulating a substantial evolution on the competitiveness of the Brazilian automotive industry.
Keywords: Brazil; Competitiveness; Flowchart approach model; New Brazilian automotive policy; Porter's diamond model